Phage Therapy for Treatment of UTI Caused by Multi-Drug-Resistant E. coli in Vitro and in Vivo Study (Iraqi Journal of Medical Sciences, 2025)
Background:    Multidrug-resistant (MDR) bacteria cause a substantial health burden. Escherichia coli (E. coli) is one of the most common causative agents of bacterial infections in urinary tract infection (UTI) and emergence of multidrug resistant E. coli is a major public health threat worldwide. In this respect, recent studies have proposed bacteriophage (phage) therapy as a potential alternative therapy to antibiotics for treating MDR bacteria.Objective:    To evaluate the potential of bacteriophage therapy to treat a drug-resistant UTI caused by E. coli in rabbits. Methods: This study was carried out during the period from September 2019 to February 2021 in Kirkuk Province. A total of 30 bacterial isolates of E. coli were collected from bacteriology isolated - clinical specimens. Full diagnostic procedures were conducted to confirm the diagnosis of E. coli; moreover, antibiogram was done to identify MDR E. coli isolates. Lytic phages were isolated using phage amplification assays. Phage cocktail was prepared accordingly. Rabbit animals with induced UTI were orally fed with E. coli specific phage cocktail. Phages and E. coli bacteria were isolated from urine of rabbits for evaluating the success rate of phage therapy.Results: It was shown that four bacteria isolates did establish specific lytic phages for E coli. Orally-fed phages to E. coli were isolated from the urine of rabbits and peaked at the second day with continuous decline in titer over the third and fourth days after phage administration. The average titer plaque-forming unit/ml (PFU/ml) for E. coli specific phages was 46, 15 and 1 at the second, third and fourth days. Regarding the in vivo activity of phage on bacterial growth, the bacterial count in urine was shown to decline remarkably after 24 hr till 4 days after the oral administration of lytic phages. The decline in bacterial count in urine was highly significant and reached up to 7-8 log.  Conclusion: Phage cocktail therapy was shown to be effective in treating uropathogenic MDR E. coli and bacteriophage therapy was safe during this study and no side effects were observed.Keywords: MDR, plaque-forming unit (PFU), colony-forming unit (CFU), phage therapy, E. coli, bacteriophageCitation: Saqi HN..  Abdul Ameer AS. Phage therapy for treatment of UTI caused by multi-drug-resistant E. coli in vitro and in vivo study. Iraqi JMS. 2025; 23(1): 184-189. doi: 10.22578/IJMS.23.1.22